Nutrients for Yeast Growth on Grape Berry Exudates - Prakitchaiwattana, Cheunjit; Fleet, Graham H.; Heard, Gillian M. (Food Agricultural Sciences and Technology, 2020)
This study presents data from analyses of sugars, organic acids and amino acids in rinses from the surfaces of grapes and their impacts on yeasts associated to the surfaces. Results obtained demonstrated that the grape surfaces contain basic nutrients; sugars (glucose and fructose), amino acids (i.e. proline, arginine, threonine, and phenylalanine) and organic acids (oxalic, citric, tartaric, malic, and citric, succinic and acetic acids) that could support the growth of yeasts. The surface concentrations increased as the grapes matured and, consequently, the yeast population also increased. Damaged grapes had much higher concentrations of surfaces accessible sugars and amino acids, and would explain the very high populations normally found on such grapes. Yeast populations increased with the availability of sugar, suggesting growth-substrate relationship. Aureobasidium pullulans was the most prevalent species on undamaged and damaged berries of both Shiraz and Chardonnay grapes throughout cultivation from every vineyard in the year 1 and 2 seasons. Results obtained from this study could be an important information for better understanding microbial ecology associated to fruit surfaces. The information obtained was important for the development of pre-and post-harvest processes in industrial fruit production.